Acceptance of the System and Perceived Risk in the Use of the Accurate Accounting Information System - Larasati; Baridwan; Roekhudin (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The adoption of accounting information systems in higher education is critical for improving efficiency, transparency, and accountability, particularly in institutions transitioning to autonomous entities. This study investigates the determinants of behavioral intention and use behavior in the adoption of the accurate accounting information system, integrating the Unified Theory of Acceptance and Use of Technology with perceived risk variables. Data were collected from business unit staff using a structured survey, with 220 responses analyzed via Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results reveal that effort expectancy, social influence, facilitating conditions, and low perceived risks positively affect behavioral intention, while experience and voluntariness moderate several relationships. Behavioral intention significantly predicts actual system use. These findings highlight that ease of use, organizational support, social encouragement, and risk perceptions are key drivers of accounting information system adoption. Practically, managers should enhance training, strengthen technical and organizational support, and implement communication strategies to reduce perceived risks, thereby fostering consistent system use. The study contributes theoretically by extending Unified Theory of Acceptance and Use of Technology with financial and temporal risk considerations, offering insights for technology adoption in higher education settings.